Systematic Literature Review: Kesulitan Belajar Mahasiswa Pendidikan Matematika - Auliya Amanda; Rusi Ulfa Hasanah; Siti Nurmala (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This research is motivated by the fact that mathematics education students generally experience various problems in attending lectures. The aim of this research is to determine the factors of learning difficulties for mathematics education students. Many studies have been conducted to find out what difficulties mathematics education students experience in learning. This research aims to collect, identify, evaluate, analyze, interpret and conclude various similar studies that discuss the learning difficulties of mathematics education students. The research method uses SLR (Systematic Literature Review). The results of this research are divided into four parts according to the research questions studied from 15 articles relevant to the research topic. The four parts are what the learning difficulties of mathematics education students are, the causes, consequences, and solutions that can be applied to overcome these problems. The factors of student mathematics learning difficulties consist of 12 factors, namely; 1) the influence of student psychology; 2) the factor that students are often sleepy; 3) eye sight; 4) playing on cellphones with friends who like to skip lectures; 5) learning media that causes students to be lazy about studying; 6) lecturers are often angry 7) students often do not complete assignments; 8) lack of control by lecturers; 9) Unwillingness of student ATK; 10) Boring lecturer teaching methods; 11) Learning activities that only take notes so that students are lazy and play a lot; 12) lack of cooperation between students.